Turtle Biology Conservation at Taman Kili Kili Beach, Wonocoyo Village - Juliaeta AB Mamesah; Maureen A Tuapattinaja; J. M. S Tetelepta; Mintje Wawo; Fadila Salma (Jurnal Penelitian Pendidikan IPA, 2024)
Conservation is one of the activities that is expected to prevent the extinction of turtles and turtle habitats, preventing the use of turtles for commercial purposes such as selling their eggs, meat, and shells. This research was carried out in the Taman Kili Kili Beach area from January to March 2022. This research aimed to determine the management carried out at Taman Kili Kili Beach and the sustainability of turtle conservation at Taman Kili Kili Beach. The data analysis in this research is an initial analysis consisting of qualitative and quantitative analysis, while further analysis is a Rapfish analysis. The results of the research show that the management of turtles in the Kili-Kili Park Turtle Conservation area carries out several activities: Searching for turtle eggs, breeding process, hatchling rearing process, and releasing hatchlings into the sea. Sustainability based on the results of Rapfish for Conservation at Taman Kili Kili Beach is categorized as sustainable, but more attention needs to be paid to the institutional and infrastructure dimensions.